In vitro interleukin-6 release in whole blood cultures in samples taken at rest from triathletes and professional rugby players - Pool, E. J.; Robson, P. J.; Smith, C.; van Wyk, J. H.; Myburgh, K. H. (European Journal of Applied Physiology, 2002)
The aim of this study was to investigate the endotoxin-induced interleukin-6 (IL-6) release in whole blood cultures from samples taken at rest, 24 h post-exercise, from a control group of recreationally trained individuals (C), a group of highly trained triathletes (TA) and a group of highly trained professional rugby players (RP). Fifteen RP [mean (SD): age 26 (3) years, height 1.90 (0.2) m, body mass 104.5 (12.2 kg)], 13 male TA [age 33 (5) years, height 1.78 (0.1) m, body mass 76.3 (12.6) kg] and eight recreationally active male volunteers [age 28 (6) years, height 1.80 (0.1) m, body mass 72.3 (7.3) kg] participated in the study. Plasma IL-6 concentration and in vitro IL-6 synthesis by whole blood cultures were measured in samples taken at rest. Plasma IL-6 concentration was significantly higher (P<0.01) for the RP and TA groups than for C, as were the in vitro basal and endotoxin activated concentrations. However, after endotoxin stimulation, newly induced IL-6 concentration was significantly lower (P<0.01) in the RP and TA than in the C group. Therefore, professional rugby players have a similar IL-6 release of whole blood cultures in vitro to that of triathletes. Specifically, mononuclear cells appear to be chronically activated to spontaneously release IL-6, but have a decreased capacity to respond to a further stimulus. Amongst possible explanations for this, the most likely is counter-regulation due to already elevated IL-6 release.